2019
DOI: 10.3390/ijerph16245119
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Space on Violent Crime in Urban Environments: An Evidence Synthesis

Abstract: Can the presence of green space in urban environments reduce the frequency of violent crime? To ascertain the evidence on this topic, we conducted an in-depth literature review using the PRISMA checklist. The search parameters included US articles written in English and published since 2000. More than 30,000 potential paper titles were identified and ultimately, 45 papers were selected for inclusion. Green spaces typically comprised tree cover, parks and ground cover. Criminal behaviors typically included murd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 95 publications
(109 reference statements)
1
55
1
Order By: Relevance
“…Our results are in line with previous research findings, which uncovered negative associations between greenspace and crime 10,11,16,35,36 . However, our 'physical presence of greenspace' variables (i.e., Tree Canopy, Grass Coverage) had weaker and less consistent associations with reduced crime, compared to our 'use of greenspace' variable (i.e., Park Visits).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with previous research findings, which uncovered negative associations between greenspace and crime 10,11,16,35,36 . However, our 'physical presence of greenspace' variables (i.e., Tree Canopy, Grass Coverage) had weaker and less consistent associations with reduced crime, compared to our 'use of greenspace' variable (i.e., Park Visits).…”
Section: Discussionsupporting
confidence: 93%
“…A growing body of research examines the impact of the physical environment on crime, through such features as climate 6 , vacant lots or buildings 7 , ambient and artificial light 8 , or disorder 9 . Another factor that has been much less studied is the impact of urban greenspace 10 .…”
mentioning
confidence: 99%
“…4c ). The greening of cities would have resulted from more urban parks or green spaces, which are likely to have multiple benefits for the urban environment and human health/well-being, including improving cardiovascular conditions 31 , 36 , and mental health 32 and reducing crime and violence 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research examines the impact of the physical environment on crime, through such features as climate (6), vacant lots or buildings (7), ambient and artificial light (8), or disorder (9). Another factor that has been much less studied is the impact of urban greenspace (10). Some research has demonstrated a negative relationship between crime levels and various types of urban greenspace, such as tree canopy (11), vegetation levels (12), and greened lots (13), while others have failed to find a relationship between greenspace and crime at all (14).…”
Section: Introductionmentioning
confidence: 99%